2019
DOI: 10.4094/chnr.2019.25.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceptions of Death, End-of-Life Care Stress, and Emotional Intelligence on Attitudes towards End-of-Life Care among Nurses in the Neonatal Intensive Care Unit

Abstract: The purpose of this study was to investigate the influence of perceptions of death, end-of-life (EOL) care stress, and emotional intelligence on attitudes toward EOL care among nurses in the neonatal intensive care unit (NICU). Methods: The participants were 111 nurses working in a NICU who had experienced EOL care at least once. Data were analyzed using the t-test, Pearson correlation coefficient, and stepwise multiple regression analysis in SPSS for Windows. Results: The mean score for perceptions of death w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Not surprisingly, our study also found that nurses who work at ICU and palliative care units were more likely to perform EOL care than those who work in general wards. From the nature of ICU or palliative care units, patients there are more likely to face EOL cases than in other units [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, our study also found that nurses who work at ICU and palliative care units were more likely to perform EOL care than those who work in general wards. From the nature of ICU or palliative care units, patients there are more likely to face EOL cases than in other units [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Attention to education around the specific needs of the dying child and their family has had less attention than those in the adult population. Well-trained, better-prepared nurses are in the best position to provide expert EOL care to pediatric patients and their families (Park & Oh, 2019). For hematology/ oncology nurses, while death is not something that is faced daily, it is a reality that all nurses in this specialty must face.…”
Section: Implications For Hematology/oncology Nursingmentioning
confidence: 99%
“…For nurses, the experience of a beautifully facilitated death of a patient can be extremely fulfilling. According to Park and Oh, “[s]ufficient preparation for EOL care and positive attitudes may facilitate a decent and dignified life and death for the patient and his or her family” (2019). Pediatric hematology/oncology nurses have the honor of walking with families during the worst times in their lives.…”
Section: Implications For Hematology/oncology Nursingmentioning
confidence: 99%
“…22 However, several studies found that Korean nurses reported low levels of knowledge, passive attitude, and high stress on palliative care provision, raising the need for palliative care education and protocol. 10,14,15,23 The palliative and end-of-life care guidelines developed in Western countries cannot be directly applied to nurses in the Korean NICU for several reasons: differences in the NICU physical environment; nurse staffing ratios; laws on life-sustaining treatments; and the cultural, religious, and social backgrounds of nurses and parents.…”
Section: Introductionmentioning
confidence: 99%